Mendesain Ulang Pembelajaran Sains Anak Usia Dini yang Konstuktif Melalui Steam Project-Based Learning Yang Bernuansa Islami - Muhamad Imaduddin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: The amount of early childhood’s curiosity against what exists in nature should be facilitated through science lessons. Various problems including the lack of knowledge and strategies of educators to teach science concepts have become issues that are often discussed. That becomes interesting is how to adapt and design learning science more constructive and meaningful for the early childhood. One alternative is through project-based learning that integrates components of STEAM and Islamic values as a form of the main purpose of early childhood islamic education. Initial studies of this research is to use the results of empirical observation and viewing documentation science teaching and learning in Indonesia. Furthermore, theoretically be replicated through literature searches related to science learning and teaching materials. Phenomenological approach is used to reveal and redesign the necessary science concepts in Islamic education of early childhood. The results indicate that 1) the necessary of changes in the perspective of educators, initially inclined as behaviorist educators become constructivist educators in the teaching of science, 2) there are islamic themes that can be integrated with STEAM through simple projects for science learning of early childhood which include life sciences, earth and space science, and physical scienceKeywords: Science Lessons, Constructive, Early Childhood, STEAM, Project-Based Learning